Staphylococcus aureus on Sinus Culture Is Associated With Recurrence of Chronic Rhinosinusitis After Endoscopic Sinus Surgery - Maniakas, Anastasios; Asmar, Marc-Henri; Renteria Flores, Axel E.; Nayan, Smriti; Alromaih, Saud; Mfuna Endam, Leandra; Desrosiers, Martin Y. (Frontiers in Cellular and Infection Microbiology, 2018)
Objectives: Identify whether identification of S. aureus on conventional culture is a predictor of success or failure after ESS followed by budesonide nasal irrigations (BUD) in chronic rhinosinusitis (CRS) patients at high risk of recurrence. Methodology: Prospective clinical trial including 116 patients from a tertiary care center at high-risk of disease recurrence following ESS+BUD. Blood samples, microbial swabs, and SNSS/SNOT-22 were taken on the day of surgery (Visit-1) and 4 months postoperatively (Visit-2). Outcomes were evaluated using symptoms and mucosal status as assessed by the Lund-Kennedy endoscopic score. Results: Seventy-five patients (69.4%) attained SNOT-22 MCID or higher. (Mean = 33.4, range 9–75). Objective documentation of recurrence of disease, as defined by combined endoscopic/symptomatic criteria, was noted in 58/116 patients (50%). Revision surgery was associated with a significantly higher rate of disease recurrence (60.0 vs. 28.0%; p < 0.001). Culture for Staphylococcus aureus was associated with disease recurrence, preoperatively and at 4 months post-surgery (p = 0.020; p < 0.001). This was restricted to post-operative cultures in the revision group (10.0 vs. 48.8%; p < 0.001). Other factors associated with poor outcome included intolerance to non-steroidal anti-inflammatory drugs (NSAID) (p = 0.036). Significantly higher Lund-Kennedy scores in the recurrence groups despite similar symptom intensity, emphasizing the importance of considering objective outcome in addition to patient-reported ones. Conclusion: Patients undergoing revision ESS are at high risk of disease recurrence, even when budesonide irrigations are used post operatively. Presence of S. aureus on culture pre-operatively or at 4 months post-ESS is associated with a negative outcome. This suggests that S. aureus negatively influences outcome, possibly via a number of mechanisms, including interactions with the (i) immune system, (ii) regeneration and repair of the sinus epithelium, or (iii) via interference with the sinus microbiome. This suggests that S. aureus may be a simple and inexpensive biomarker for disease severity and indicates a clear need to better appreciate S. aureus on how it contributes mechanistically to disease development and persistence in order to develop targeted therapeutic strategies.